Inzidenz von Kniegelenkverletzungen: Zahlen für die ambulante und stationäre Versorgung in Deutschland = Incidence of knee injuries : numbers for outpatient and inpatient care in Germany - Schneider, Olaf; Scharf, Hanns-Peter (Der Orthopäde, 2016)
BackgroundMusculoskeletal illnesses and injuries are among the most common ailments in the Federal Republic of Germany. In 2008 they generated costs of nearly 29 billion euros. Figures about their incidence and prevalence are necessary for a demand-oriented planning of future patient-centred care.MethodPseudonymised data of 3.8 million people insured by AOK Baden-Württemberg between 2008 and 2013 were evaluated. The diagnoses were assigned to nine injury groups. For outpatient care confirmed diagnoses were considered, and for inpatient care both primary and secondary diagnoses were considered. For all patients with structural knee injuries, it was evaluated whether they made use of one of five eligible treatment paradigms either in the quarter in which they were injured or in the following quarter.Results418,257 patients were treated in 2013 for at least one new-onset injury (10.9 % of all insurees); 86,783 insurees (2.3 % of all insurees) had a newly occurring knee injury. The vast majority of the patients were treated by specialist doctors. While magnetic resonance imaging clearly increased during the observation period, the incidence of surgical therapy did not change. Striking are the different age distributions regarding the types of injuries, with a high injury incidence amongst young men and a significant increase in injuries between 2008 and 2013, especially amongst women.ConclusionFor the first time, the data quantify the knee injury incidences of a large cohort in Germany. They show which inpatient and outpatient health care services have been claimed and that an age- and gender-adapted prevention and an increased awareness are needed.
Gesehen am 10.04.2019